Repeating purposefully: Empowering educators with functional communication models of echolalia in Autism. (April 2022) - Cohn, Eli G.; McVilly, Keith R.; Harrison, Matthew J.; Stiegler, Lillian N.
Background and Aims: Echolalia, the repetition of speech, is highly prevalent in school aged children with Autism. Prior research has found that individuals with echolalia use their repetitions to engage in communicatively functional speech, in the absence of self-generated speech. Educators are the natural audience for a wide vary of echoed utterances across environments and in differing contexts. The objectives of this paper were three-fold: (1) to systematically investigate how researchers identify and ascribe communicative function to echoed utterances; (2) to gather and evaluate the evidence that might assist teachers to identify and better understand echoed utterances as being communicatively purposeful; and (3) to provide teachers with evidence-informed response strategies they can use to assist their students on their journey towards more self-generated speech. Main Contribution: Prior research in the field of echolalia has generally been segmented into opposing viewpoints. A paucity of work in the echolalia field has meant that there is limited work that has sought to view how a communicative function to echolalia has been ascribed from across multiple disciplines and fields. As such, there is limited literature to guide the practice of classroom educators. This review combines communicative models from across various disciplines with the view to supporting classroom educators by providing guidance on how they might assist their students with echolalia. This review represents the first contribution to the research literature in this area. Conclusions and Implications: Research into echolalia did not originally emanate from the field of education; however, anecdotes from classroom educators were cited as the primary impetus for the creation of some of the communicatively functional models. We found that although there are many techniques that researchers have used to attribute a communicative function to echolalia, some of these can be easily employed by educators in their practice. By adopting these techniques, educators are placed in a position that may assist with the identification of communicative echolalia; subsequently they are better placed to acknowledge and respond to their students.